A252 FUNCTIONAL ANALYSIS OF GENETIC AETIOLOGIES IN A DOWNSTREAM OF TYROSINE KINASE (DOK) PROTEIN IN THE PATHOGENESIS OF PEDIATRIC INFLAMMATORY BOWEL DISEASE (IBD). (26th February 2020) - Batura, V; Guo, C; Warner, N; Leung, G; Ricciuto, A; Muise, A
Abstract: Background: IBD is a form of chronic inflammatory disorder of the gastrointestinal tract that arises due to genetic, environmental, immunological and microbial factors. The precise pathological mechanisms remain elusive. It is thought that the onset of pediatric IBD can largely be attributed to genetics. Muise lab, at SickKids, regularly screens children at the SickKids IBD clinic and through an international consortium to find possible genetic links to the disease. We report a patient at SickKids with biallelic mutations in DOK4 who has severe Crohn's Disease along with other inflammatory conditions. Downstream of kinase (DOK) proteins are a family of adaptor molecules that serve as scaffolding proteins important in regulating cell signaling, especially in T cells. DOK4 has been shown to have negative regulatory effects on T cell activation but is also expressed across various other tissues where its function is yet to be determined. We predict that these mutations are causing immune cell dysregulation, which may be contributing to the patients IBD. Aims: Through this study, we aim to enhance our understanding of the pathobiological mechanism of novel mutations in DOK4 . Methods: We have established T cell lines, expressing wild type and mutated DOK4, which will be used to perform functional tests, such as localization analysis through immunofluorescence and cytokine profiling, to check for T cell function. We have patient derived organoids, which will be used to assess changes in gut morphology using imaging techniques. We will also generate mutant zebrafish model that will be used to determine the susceptibility to colitis related to this mutation, disease progression and gut peristalsis using live imaging technology. Results: Preliminary data shows variation in expression of the protein within patient derived peripheral blood mononuclear cells (PBMCs) compared to a healthy donor. Conclusions: With this study, we hope to identify new therapeutic targets for patients with DOK4 mutations. Funding Agencies: CIHRThe Leona M. and Harry B. Helmsley Charitable Trust